PENGARUH TINDAKAN SUPERVISI, KOMITMEN PROFESIONAL DAN KOMITMEN ORGANISASIONALTERHADAP KEPUASAN KERJA AUDITOR BPKP PERWAKILAN DAERAH RIAU - Rizky Andrian; Nur Azlina; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to test empirically the effect of actions that supervision, professional commitment and organizational commitment on job satisfaction auditors. The population in this study is the Public Sector Auditors who worked in Various Government Agencies Prov. Riau. sample in this study consisted of Auditor Candidate totaling 18 people, numbering Executive Auditor totaled 18 people, Implementing Advanced Auditor numbered 1, Auditor Supervisor of 20 people, first auditr amounted to 4 people and young auditors and auditors of 35 people associate amounted to 14 people. The total sample in this study amounted to: 110 people. Analysis of research on the use is to use multiple linear regression equation with SPSS (Statistical Product and Service Solutions). The results showed that the supervision Based on the results of action research which is represented by the leadership and mentoring aspects significantly influence job satisfaction auditors. Supervision actions are represented by the aspect of working conditions, no significant influence on job satisfaction auditors, supervision actions represented by assignment aspects significantly influence job satisfaction auditors. Professional commitment significant effect on job satisfaction auditor at BPKP Prov. Riau. And organizational commitment has no effect on job satisfaction.Keywords: Action Supervision, Professional Commitment, Organizational Commitment and Job Satisfaction